Analysis of the law and practice governing letter of credit: A case study of selected institutions in Ilala Dar es salaam - Otieno, Magreth (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of Master’s Degree in Commercial Law (LL.M. CM.) of Mzumbe University